Lorentz force metamaterial with giant optical magnetoelectric response - Valente, João (2018)
We demonstrate the first reconfigurable photonic metamaterial controlled by electrical currents and magnetic fields, providing first practically useful solutions for sub-megahertz and high contrast modulation of metamaterial optical properties.